Pengaruh Literasi Digital dan Keterampilan Digital Wirausaha Wanita Terhadap Kinerja UMKM di Kabupaten Purbalingga - Agustin Riyan Pratiwi; Dyah Supriyatin; Retno Pangestu; Adelia Fatwa Meautia Putri (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The entrepreneurial world has entered the digital era, prompting MSMEs to embrace the digital realm. With 37 million female entrepreneurs in Indonesia, most of whom operate micro-businesses, there is a pressing need for special attention to be given to digital literacy and skills. This is crucial for enhancing business performance by leveraging their potential through digital skills and knowledge. This has been evidenced by research involving 72 female entrepreneurs who own MSMEs in Purbalingga Regency. The study utilized a quantitative approach with Regression Analysis tested using SPSS 25.0. The results indicate that digital skills and literacy significantly influence the performance of MSMEs, highlighting the importance of efforts to enhance digitalization skills and knowledge among female entrepreneurs in Purbalingga.